A preliminary study on the Earth's evolution and condensation. (12th March 2021) - Guo, Shaofeng; Zheng, Jianmin; Qiao, Guohua; Wang, Xudong
ABSTRACT: Through many field geology observations, the authors find that sandstone and carbonate rocks, which were originally thought to be sedimentary, have magmatic characteristics and should classified as magmatic rather than sedimentary rocks. Combining this information with the principles of Bowen's reaction series, the authors infer that the Earth has evolved gradually from high temperature to low temperature and, through crystallization differentiation, has experienced the following stages: high melting point metal to ultramafic rock to mafic rock to neutral rock to acidic rock to sandstone to carbonate rock to mudstone to ice. Since fossils that preserve the remains of creatures, such as fossil fish, occur in magmatic rocks rather than sedimentary rocks, the organisms were not aquatic but lived in high-temperature fluids with magmatic characteristics. Therefore, the authors conclude that during the evolution of rocks from high temperature to low temperature, biological evolution from high temperature to low temperature also occurred on the Earth and that carbon-based life did not originate in the ocean but in high-temperature carbon-containing fluids; this is a subversive statement. This understanding contradicts the original interpretation, that is, that fossils formed under normal temperature and pressure conditions. This point explains the Cambrian explosion and later mass extinctions.